SISTEM PENDUKUNG KEPUTUSAN PENERIMA BEASISWA PPA PADA FAKULTAS TEKNIK UNIVERSITAS PALANGKA RAYA - Karolita, Devi; Marhayu, Marhayu; Berto, Sund (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2017)
Scholarship is a grant that is given to an individual person who is still taking education, tohelp the students to support their tuition fee. A decision support system for the scholarship distributionis needed to select the right students that will get the grant.This decision support system is using the Simple Additive Weighting (SAW) Method. WithSAW method, hopefully the assessment will be more accurate since it is based on predeterminedcriteria and weight that will get the more accurate result on who will get the scholarship.The testing of aplication is done by giving a questionnaire that filled by users of theapplication, some users declare conformity with this aplication, but a few users find difficulty with theapplication. The result of system analysis indicates that 98.2% is appropriate and 1.8% is notappropriate. This Decision of scholarship recipient Support System needs to be made on the webbasic to facilitate the deployment.